Measures to prevent and resolve conflicts of interest in public authorities in the Russian Federation and foreign countries - S. G. Eremin (Управленческие науки)
The article is aimed at studying of measures to prevent and resolve conflicts of interest in public authorities in the Russian Federation and foreign countries. The task of the study is to analyze the list of methods to resolve conflicts of interest in public authorities in Russian and foreign legislation, with an emphasis on the need for its concretization and clarification of the boundaries of the applicable legal technique, and finding an alternative to the list. The article offers an instrumental basis for clarification of gradation of ways of exit from the real conflict of interests. The thesis is argued that indicating measures to prevent and resolve conflicts of interest in public authorities in Russian legislation is advisable to legally delineate and formalize them consistently, defining specific forms, stages and mechanisms for solving the problem, based on foreign practice, recommendations are made to prevent conflicts of interest in public authorities.